Surface-initiated reversible addition fragmentation chain transfer of fluoromonomers: an efficient tool to improve interfacial adhesion in piezoelectric composites. Issue 42 (20th October 2022) - Bouad, Vincent; Ohno, Kohji; Addad, Ahmed; Marin, Adeline; Donzel, Nicolas; Barrau, Sophie; Lyskawa, Joël; Ladmiral, Vincent
Abstract : Baryum titanate/P(VDF- co -TrFE) piezoelectric composites with sturdy interfaces thanks to surface-initiated RAFT polymerization prepared fluoropolymer brushes. Abstract : This article reports the surface-initiated Reversible Addition–Fragmentation chain Transfer polymerization (SI-RAFT) of trifluoroethylene (TrFE) and vinylidene fluoride (VDF) from barium titanate nanoparticles (BTO NPs) for the preparation of piezoelectric composites. A new xanthate chain transfer agent (DOPA-XA) derived from O -ethyl- S -(1-methoxy-carbonyl) ethyldithiocarbonate and integrating a catechol moiety able to efficiently bind onto the BTO NP surface was synthesized, characterized via 1 H and 13 C NMR spectroscopy and employed to mediate SI-RAFT polymerizations. This DOPA-XA was immobilized onto BTO NPs and the grafting efficiency was evaluated by TEM images and XPS measurements while the grafting density ( Γ > 0.2 chains per nm 2 ) was calculated using TGA and BET measurements. Poly(trifluoroethylene)- (PTrFE) and poly(vinylidene fluoride- co -trifluoroethylene)- (P(VDF- co -TrFE) functionalized BTO NPs were prepared by SI-RAFT polymerization and characterized by nuclear magnetic resonance (NMR), size exclusion chromatography (SEC), thermogravimetric analysis (TGA), transmission electron macroscopy (TEM) and X-ray photoelectron microscopy (XPS). Interestingly, polymer brushes featuring relatively low dispersities ( Đ < 1.5) and high grafting densities ( Γ > 0.2 chains per nm 2 ) were obtained. Piezoelectric composite films were then prepared from these fluoropolymer-decorated BTO NPs by incorporation into a P(VDF- co -TrFE) matrix using the solvent casting method. The homogeneity of the NPs dispersion in the copolymer matrix was assessed by SEM and the direct piezoelectric response of the composites was recorded after polarization and compared with composites prepared from non-modified BTO NPs. The measured piezoelectric coefficients ( d 33 ) of all the composites were of the same order of magnitude (around −9 pC N −1 ). Finally, the interface between the NPs and the copolymer matrix was mechanically stressed by stretching. The SEM images of the composite fracture showed, in the case of nongrafted BTO NPs, the presence of cavities close to the NPs associated with a weak interfacial adhesion while, for fluoropolymers grafted BTO NPs, the interface with the copolymer matrix was cohesive. This study leads to innovative composites with a cohesive ceramic/polymer interface for piezoelectric applications.